Síntese e caracterização de biocompósitos hidroxiapatita/colágeno dopado com zinco - Maria Helena Santos (2005)
Santos, M.H. Synthesis and characterization of calcium phosphates/collagen biocomposites doped with zinc. Thesis (Doctorate in Metallurgical and Mines Engineering, area of concentration Scienceand Engineering of Materials) - School of Engineering, Federal University of Minas Gerais, 2005. Just now, a great challenge is the development of biocompatible materials for economically feasible processes. In this study were developed calcium phosphate/collagen composites doped with zinc for application in bone regeneration. Hydroxyapatite and hydroxyapatite-tricalcium phosphate were synthesized having calcium hydroxide and orthophosphoric acid as precursors. The Ca/P molar ratiowas fixed at 1.67 and were varied synthesis parameters as chemical and heat treatments. Hydroxyapatite and hydroxyapatite--tricalcium phosphate were synthesized and doped with zinc nitrate during the synthesis. The collagen, extracted from bovine pericardium, was submitted to the enzymatic digestion and purified by ion-exchange chromatographic method. High purity grade type I collagen (COL) was obtained, dialyzed, characterized by electrophoresis and lyophilized.Hydroxyapatite and hydroxyapatite-tricalcium phosphate composites were produced with collagen, by sing the ratio 80/20 (CaP/COL, weight%). Also, they were doped with zinc by using Zn(NO3)2 salt.All samples were characterized by chemical analysis, light and scanning electron microscopy, X-ray diffraction and infrared spectroscopy. The composites presented morphologic and structural characteristics similar to their constituent materials. The biological evaluation of the composites in vitro showed cellular viability, presenting proliferation and production of alkaline fosfatase of the osteoblasts. Probably, the developed biocomposites can be used for rebuilding bone tissue in thefuture.